Is There a Role for Liver Transplantation in Non-Colorectal Liver Metastases? - Herden, Uta (Viszeralmedizin, 2015)
Due to the high blood flow, especially blood from the intestinal tract via the portal vein, the liver is a preferred organ for metastases. In case of advanced, irresectable liver metastases liver transplantation (LTX) remains an attractive option. However, due to high recurrence rates or a lack of data, up to date, metastases from neuroendocrine tumors (NETs) are the only accepted indication for LTX in non-colorectal liver metastases. In this regard, LTX is only justified in patients in which complete tumor resection (R0 resection) of the NET is achievable. A literature review revealed no clear patient selection criteria but transplantation should definitively achieve an R0 resection with complete freedom of tumor. The available data regarding the outcome following LTX for NETs show a comparable short- and long-term outcome for patients transplanted for other malignancies, e.g. hepatocellular carcinoma, or also benign indications in the high MELD (model for end-stage liver disease) era. Thus, most data prove a better post-transplant outcome and a lower recurrence rate in patients with a good differentiation of the tumor, a low proliferation index (Ki67), and a portal drainage of the NET.